2000
DOI: 10.1115/1.1287267
|View full text |Cite
|
Sign up to set email alerts
|

Rough Wall Turbulent Boundary Layers in Shallow Open Channel Flow

Abstract: An experimental study was undertaken to investigate the effects of roughness on the structure of turbulent boundary layers in open channels. The study was carried out using a laser Doppler anemometer in shallow flows for three different types of rough surface, as well as a hydraulically smooth surface. The flow Reynolds number based on the boundary layer momentum thickness ranged from 1400 to 4000. The boundary layer thickness was comparable with the depth of flow and the turbulence intensity in the channel fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
52
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(61 citation statements)
references
References 31 publications
8
52
0
1
Order By: Relevance
“…Keirsbulck et al (2002) studied the structure of a turbulent boundary layer over fully rough k-type two-dimensional square bars at Re 0 = 8500. Similar to the studies of Tachie et al (2000), it was observed that the magnitude of the wake strength is increased by the roughness. In the near-wall region, the contribution to the Reynolds shear stress fraction and the diffusion factors were found to depend on the wall roughness conditions.…”
Section: "Outside the Roughness (Or Viscous) Sublayer The Turbulent supporting
confidence: 80%
See 2 more Smart Citations
“…Keirsbulck et al (2002) studied the structure of a turbulent boundary layer over fully rough k-type two-dimensional square bars at Re 0 = 8500. Similar to the studies of Tachie et al (2000), it was observed that the magnitude of the wake strength is increased by the roughness. In the near-wall region, the contribution to the Reynolds shear stress fraction and the diffusion factors were found to depend on the wall roughness conditions.…”
Section: "Outside the Roughness (Or Viscous) Sublayer The Turbulent supporting
confidence: 80%
“…However, the notion of a universal velocity defect law for arbitrary roughness has been questioned by several recent studies (Shafi & Antonia, 1997;Krogstad & Antonia, 1999;Keirsbulck et al, 2002;Tachie et al, 2000Tachie et al, , 2003Poggi et al, 2003;Bhaganagar et al, 2004).…”
Section: (3)mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, many rough-wall turbulence studies exhibit such similarity in the single-point statistics, both for flow over idealized surfaces (Raupach, 1981;Ligrani and Moffat, 1986;Bandyopadhyay and Watson, 1988;Flack et al, 2005;Bakken et al, 2005;Kunkel and Marusic, 2006, among others) as well as for flow over more irregular topographies (Allen et al, 2007;Mejia-Alvarez and Christensen, 2010b). In contrast, other studies report single-point statistics affected by roughness well into the outer layer (Krogstad et al, 1992;Krogstad and Antonia, 1999;Keirsbulck et al, 2002;Tachie et al, 2000Tachie et al, , 2003. However, most of these efforts had weak scale separation between the roughness and the outer length scale of the flow, yielding δ/k and/or δ/k s values well below the thresholds proposed by Jimenez (2004) and Flack et al (2005).…”
Section: Introductionmentioning
confidence: 97%
“…This system relies upon the measurement of the Doppler frequency shift of light scattered from an illuminating laser beam by particles entrained within the flow. It has also been widely used for open channel laboratory turbulence measurements (Ali et al 2013;Buchhave et al 1979;Nakagawa and Nezu 1987;Nezu and Rodi 1986;Nezu and Sanjou 2011;Tachie et al 2000;Tominaga and Nezu 1991), but it is infrequently used under field conditions because of its size. Deterioration of optical transmissions due to turbidity and higher cost also make its use lesser (Agrawal and Aubrey 1992;Agrawal and Belting 1988).…”
Section: Laser Doppler Velocimeter (Ldv)mentioning
confidence: 99%